2012
DOI: 10.1016/j.biochi.2011.12.002
|View full text |Cite
|
Sign up to set email alerts
|

tRNA-like elements in Haloferax volcanii

Abstract: All functional RNAs are generated from precursor molecules by a plethora of processing steps. The generation of mature RNA molecules by processing is an important layer of gene expression regulation catalysed by ribonucleases. Here, we analysed 5S rRNA processing in the halophilic Archaeon Haloferax volcanii. Earlier experiments showed that the 5S rRNA is cleaved at its 5' end by the endonuclease tRNase Z. Interestingly, a tRNA-like structure was identified upstream of the 5S rRNA that might be used as a proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The crRNA is derived from the Haloferax CRISPR locus C and contains spacer 1 of this locus. The t-element is a tRNA-like structure that has been previously detected directly upstream of the 5 S rRNA in H. volcanii , and it is processed by tRNase Z to generate the 5 S rRNA 5′ end ( 36 , 37 ). Generally t-elements are substrates for both tRNA-processing enzymes, the 5′-processing enzyme RNase P, and the 3′-processing enzyme tRNase Z ( 36 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…The crRNA is derived from the Haloferax CRISPR locus C and contains spacer 1 of this locus. The t-element is a tRNA-like structure that has been previously detected directly upstream of the 5 S rRNA in H. volcanii , and it is processed by tRNase Z to generate the 5 S rRNA 5′ end ( 36 , 37 ). Generally t-elements are substrates for both tRNA-processing enzymes, the 5′-processing enzyme RNase P, and the 3′-processing enzyme tRNase Z ( 36 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the ribonucleases which catalyze many key processing steps in cellular reactions remain unknown. It has been suggested that the few currently known archaeal ribonucleases may have a broader substrate spectrum and catalyze more processing steps than their bacterial and eukaryal homologs (Hölzle et al, 2012). For instance the H. volcanii tRNase Z -an endonuclease known for catalyzing tRNA 3 processing (Schiffer et al, 2002;Späth et al, 2008)has been shown to have an additional function besides tRNA processing; it is also involved in maturation of 5S ribosomal RNA (Hölzle et al, 2008).…”
Section: Discussionmentioning
confidence: 99%